2016
DOI: 10.1021/acsami.6b08082
|View full text |Cite
|
Sign up to set email alerts
|

ZnO@MnO2 Core–Shell Nanofiber Cathodes for High Performance Asymmetric Supercapacitors

Abstract: Asymmetric supercapacitors (ASCs) with aqueous electrolyte medium have recently become the focus of increasing research. For high performance ASCs, selection of cathode materials play a crucial role, and core-shell nanostructures are found to be a good choice. We successfully synthesized, ZnO@MnO core-shell nanofibers (NFs) by modification of high-aspect-ratio-electrospun ZnO NFs hydrothermally with MnO nanoflakes. High conductivity of the ZnO NFs and the exceptionally high pseudocapacitive nature of MnO nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(63 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…Moreover, previous results suggested that micropores and mesopores with sizes less than ~5 nm have lower activity at high scan rate/current densities. As shown in Figures 7c and S3 (CV curves of Cu-MnS, Cu-MnS with 1PVP and 3PVP with different scan rates), the positive and negative shifts observed at higher scan rates, which replicate the imperfect redox reaction and the loss of a few peaks, indicate partial loss of the redox reaction [38]. Figure 8a shows the GCD measurements for the resulting electrodes tested at a current density of 1 A g −1 in a 2 M KOH solution.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, previous results suggested that micropores and mesopores with sizes less than ~5 nm have lower activity at high scan rate/current densities. As shown in Figures 7c and S3 (CV curves of Cu-MnS, Cu-MnS with 1PVP and 3PVP with different scan rates), the positive and negative shifts observed at higher scan rates, which replicate the imperfect redox reaction and the loss of a few peaks, indicate partial loss of the redox reaction [38]. Figure 8a shows the GCD measurements for the resulting electrodes tested at a current density of 1 A g −1 in a 2 M KOH solution.…”
Section: Resultsmentioning
confidence: 83%
“…Within its melting point range of 220°C-400°C; the degradation of its amorphous part at ∼300°C, and the intermolecular decomposition at about 385°C were found to occur [14,15]. The crystalline part of PVA decays at 398°C [16,17], and complete decomposition to yield the carbon and hydrocarbons that led to the liberation of CO 2 gas and resulting in pure ZnO phase occurred in the temperature range of 400°C-500°C [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…[19] Moreover, electrospinning is a common technique for energy storage and delivery technology, like supercapacitors, fuel cells, and lithium-ion batteries. [12] In this study, an effective method for synthesizing perovskite-type CeMnO 3 NFs by combining electrospinning and subsequent calcination process was demonstrated. The merits of this method are (i) simple and available synthetic technique that a great variety of materials can be effectively synthesized, (ii) controllable composition for composites that a large diversity of materials can be fabricated, and (iii) cost-effective synthetic process.…”
Section: Introductionmentioning
confidence: 98%
“…However, poor electron conductivity limits its application into supercapacitors due to the low specific capacitance . As a typical semiconductor, manganese oxide has gained specific attention in electronic devices and supercapacitors thanks to its high bandgap, low cost, abundance, low toxicity, high theoretical capacitance (1370 F g −1 ), variable valence states, and stable chemical properties . As a typical rare earth based‐perovskite, the electrochemical behaviors of LaMnO 3 have been widely investigated owing to its stable thermal and structural properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation